RESEARCH OF METHODS OF DISTRIBUTION OF SEATS IN PUBLIC TRANSPORT (Computer systems and information technologies, 2022)
In large cities, especially during a pandemic, the problem of allocating seats in transport and building the most successful route is an urgent task. The study of four methods of distribution of seats in public transport. Their advantages and disadvantages are investigated. According to the results of the research, it became clear that the existing methods alone do not allow to effectively solve the problem of distribution of seats in transport, so it is necessary to either improve existing methods or develop new methods. Improving existing methods is possible by either combining several methods into one or adding certain elements that eliminate existing shortcomings or minimize their impact on the effectiveness of the method. According to the results of the research, the method of electronic seat selection has been improved in terms of adding seat weight sensors, which makes it possible to record the number of occupied seats and helps to provide information to passengers using a mobile application for free seats. The method was also further developed with the help of a mobile application that allows you to pave a route and helps you choose a convenient place to travel to your destination.
Keywords: distribution of seats in transport; infrared sensors; touch sensors; mobile application